Psychological Stress and its Relationship to Achievement Motivation Among Football Coaches - Mohammed Fakehy; Hassn Alfifi (College of Physical Education and Sport Sciences, 2023)
This study aimed to identify psychological stress and its relationship to achievement motivation among Saudi football coaches in the Kingdom of Saudi Arabia, as well as to identify the level of psychological stress and achievement motivation among Saudi coaches. In additional, to identify the statistically significant differences between the level of stress and motivation according to the variables (training experience, training license). The study used the descriptive approach using survey mothed. The study sample consisted of (132) Saudi coaches. To collect the study information, the researcher used the scale of psychological stress and achievement motivation. The results of the study showed that the level of psychological stress on Saudi football coaches in the Kingdom of Saudi Arabia was average in all aspects, except for the senior management aspect of the team with a high degree. The results of the study also showed that the motivation towards achievement among the Saudi coaches in the Kingdom of Saudi Arabia was a large degree. This study also found that there is an inverse correlation between psychological stress and motivation for achievement among the Saudi coaches in the Kingdom of Saudi Arabia, and there are no statistically significant differences between the level of stress according to the variables (training experience, training license).  Finally, this study recommends that, the coach must work according to his abilities and in proportion to the tools available to him, and set appropriate goals for these abilities in order to be able to avoid psychological stress.